A Multidisciplinary Preoperative Teaching Session for Women Awaiting Breast Cancer Surgery: A Quality Improvement Initiative. Issue 1 (August 2018) - Ibrahim, Marize; Lau, Garnet J; Smirnow, Nadia; Buono, Anna T; Cooke, Andrea; Gartshore, Kimberley; Loiselle, Carmen G; Johnson, Kyla
Purpose: Most of the breast cancer diagnoses are recommended for breast surgery. Unfortunately, many patients report preoperative anxiety, which can affect postoperative recovery. Preoperative teaching sessions have been shown to reduce anxiety and improve recovery for the patients with breast cancer. To better support the patients at our cancer center, a multidisciplinary preoperative teaching session was developed and delivered as a quality improvement initiative. Methods: Participants scheduled for breast surgery were invited to attend a group-delivered preoperative teaching session, either for breast-conserving surgery or mastectomy. The sessions were presented by a nurse, occupational therapist, and physiotherapist. Data were collected through a researcher-developed 2-item questionnaire administered before and after sessions to compare self-reported anxiety and knowledge levels, along with qualitative feedback. Results: A total of 94 participants attended the preoperative sessions, piloted over a year. The majority were scheduled for breast-conserving surgery. Wilcoxon signed rank tests showed that after session, self-reported levels of anxiety decreased, whereas levels of knowledge increased. Most participants found the session to be very helpful and would recommend it to other patients/families awaiting surgery. Conclusions: Patients awaiting surgery for breast cancer may be better supported through a multidisciplinary group teaching session by decreasing anxiety and improving knowledge related to the procedure. Future directions could explore the effect of specific session elements on anxiety, knowledge, and postoperative complications using psychometrically sound instruments and additional time points. Implications for cancer survivors: Standardization of these preoperative teaching sessions may enhance breast cancer care, reduce postoperative complications, and improve patient recovery.